2010
DOI: 10.1128/mcb.00332-10
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Transcription through a Long CAG Tract Destabilizes Repeats and Induces Apoptosis

Abstract: Short repetitive sequences are common in the human genome, and many fall within transcription units. We have previously shown that transcription through CAG repeat tracts destabilizes them in a way that depends on transcription-coupled nucleotide excision repair and mismatch repair. Recent observations that antisense transcription accompanies sense transcription in many human genes led us to test the effects of antisense transcription on triplet repeat instability in human cells. Here, we report that simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 70 publications
(104 reference statements)
3
97
0
Order By: Relevance
“…There is generally good agreement between results in our assay in human cells and those in mouse models (29)(30)(31). Among the 20 genes shown to affect CAG repeat contraction in human cells (6,27,28,31,32,37), six have been tested in a mouse model and also shown to modulate CAG repeat instability, including MSH2 (22,47,48), MSH3 (52), PMS2 (12), DNMT1 (6), CSB (20), and XPA (L. Hubert et al, unpublished data).…”
Section: Discussionsupporting
confidence: 70%
“…There is generally good agreement between results in our assay in human cells and those in mouse models (29)(30)(31). Among the 20 genes shown to affect CAG repeat contraction in human cells (6,27,28,31,32,37), six have been tested in a mouse model and also shown to modulate CAG repeat instability, including MSH2 (22,47,48), MSH3 (52), PMS2 (12), DNMT1 (6), CSB (20), and XPA (L. Hubert et al, unpublished data).…”
Section: Discussionsupporting
confidence: 70%
“…We found that induction of transcription, which efficiently destabilizes CAG repeat tracts in human cells (30,31,33,34), is not required for stress-induced production of GFP + cells. Heat, cold, hypoxic, and oxidative stress induced the same four-to fivefold increase in GFP + cells regardless of whether transcription of the GFP gene was induced by doxycycline before stress and occurred throughout the 3-d recovery period (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…To establish a link between environmental stresses and CAG repeat instability, we used a GFP-based fluorescence assay to detect repeat contractions (30). As discussed previously, repeat contractions are a good indicator of repeat instability, including expansions (31). The fluorescence assay uses GFP(CAG) 89 cells, which are derived from T-REx HEK293 cells and carry a chromosomal GFP minigene (32) with a CAG 89 tract in the middle of its intron (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The (CTG) n · (CAG) n TNR can cause DNA polymerase stuttering and form hairpin structures in vitro (4)(5)(6)(7) and in vivo (8), which lead to TNR length instability (contraction or expansion). TNR hairpins may be formed during DNA replication (8), transcription (9), and DNA repair (10). Particularly in postmitotic cells, mismatch repair (MMR) pathways are thought to play a role in TNR instability, although the precise role of human MMR in (CTG) n · (CAG) n stability in humans remains unresolved (11,12).…”
mentioning
confidence: 99%